Sulfate selective anion recognition by a novel tetra-imidazolium zinc metalloporphyrin receptor. - Cormode, D; Murray, S; Cowley, A; Beer, P (2006)
Imidazolium groups have been successfully incorporated into the structure of a "picket fence" porphyrin molecule to produce a novel tetra-imidazolium zinc metalloporphyrin anion receptor. UV/visible spectroscopic studies reveal that this receptor is selective for sulfate anions, capable of strongly complexing sulfate in competitive water-DMSO (5 : 95) solvent mixtures. Cyclic and square wave voltammetric studies demonstrate the receptor's ability to sense a variety of anions electrochemically.